MATTERS OF ENSURING MACROECONOMIC STABILITY IN ENHANCING THE ECONOMIC SECURITY OF THE AGRICULTURAL RESOURCES MARKET - Aliyev Yashnarjon Egamberdiyevich (Scholar Express Journals, 2025)
This article theoretically and practically examines issues such as improving relationships that serve to enhance the economic security of the agro-resource market operating within the country's agricultural sector and ensure macroeconomic stability
Keywords: agrarian market; market of agricultural resources; market of agricultural services